Levofloxacin and Ciprofloxacin Co-Crystals with Flavonoids: Solid-State Investigation for a Multitarget Strategy against Helicobacter pylori - Cecilia Fiore; Federico Antoniciello; Davide Roncarati; Vincenzo Scarlato; Fabrizia Grepioni; Dario Braga (MDPI AG, 2024)
In this paper, we address the problem of antimicrobial resistance in the case of Helicobacter pylori with a crystal engineering approach. Two antibiotics of the fluoroquinolone class, namely, levofloxacin (LEV) and ciprofloxacin (CIP), have been co-crystallized with the flavonoids quercetin (QUE), myricetin (MYR), and hesperetin (HES), resulting in the formation of four co-crystals, namely, LEV∙QUE, LEV∙MYR, LEV2∙HES, and CIP∙QUE. The co-crystals were obtained from solution, slurry, or mechanochemical mixing of the reactants. LEV∙QUE and LEV∙MYR were initially obtained as the ethanol solvates LEV∙QUE∙xEtOH and LEV∙MYR∙xEtOH, respectively, which upon thermal treatment yielded the unsolvated forms. All co-crystals were characterized by powder X-ray diffraction and thermal gravimetric analysis. The antibacterial performance of the four co-crystals LEV∙QUE, LEV∙MYR, LEV2∙HES, and CIP∙QUE in comparison with that of the physical mixtures of the separate components was tested via evaluation of the minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC). The results obtained indicate that the association with the co-formers, whether co-crystallized or forming a physical mixture with the active pharmaceutical ingredients (API), enhances the antimicrobial activity of the fluoroquinolones, allowing them to significantly reduce the amount of API otherwise required to display the same activity against H. pylori.